Wallerian degeneration of the corticospinal tract following multimodal high-grade glioma treatment: a case series and recommendations for radiotherapy planning - Santos, Monica D'Alma Costa; Rodrigues, Natasha Maranhão Vieira; Gibram, Franceliny; Brunelli, Julia; Campos, Ana Carolina Pinheiro; Mancini, Anselmo; Feher, Olavo; Marta, Gustavo Nader; Hanna, Samir Abdallah; Chung, Caroline; Moraes, Fabio Ynoe; Maldaun, Marcos Vinicius Calfat (Frontiers in Oncology, 2025)
IntroductionWallerian Degeneration of the Corticospinal Tract (WDCT) is a scarcely reported complication of multimodal treatment for high-grade gliomas, which, despite its potential clinical impact, may lead to severe motor dysfunction and impair quality of life.MethodologyThis retrospective case series describes 13 adult patients with high-grade gliomas treated between 2018 and 2023 who developed imaging findings consistent with WDCT after receiving multimodal treatment. Clinical and radiological data were collected from medical records; a standardized imaging follow-up or functional scoring system was not applied. Tractography was retrospectively available for two cases, enabling its incorporation into radiotherapy planning system for CST precise delineation and corresponding dose estimation.ResultsWDCT was identified in 13 out of 192 high-grade glioma patients (6.8%). Diagnosis was based on T2/FLAIR hyperintensity along the ipsilateral CST with compatible clinical symptoms. Three cases developed WDCT after reirradiation, and seven (53.8%) had received bevacizumab prior to diagnosis: two during disease progression, two for the treatment of radionecrosis, and three as prophylaxis. Clinical symptomatology was detailed to 11 patients, 72.7% presented with hemiparesis, and 36.4% had seizures. In two cases, retrospective dose-volume analysis revealed CST mean doses ranging from 25.81 Gy to 42.83 Gy.ConclusionsThis retrospective series highlights WDCT as a potentially underrecognized complication in glioma patients undergoing multimodal treatment. While etiology is likely multifactorial, radiotherapy may play a contributing role. CST delineation, when tractography is available, may support individualized treatment planning, enable better assessment of dose exposure, and help identify patients at higher risk of motor decline. Further prospective studies are warranted to define dose thresholds and assess functional outcomes.